2015
DOI: 10.33818/ier.278039
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inflation on Inflation Uncertainty in the G7 Countries: A Double Threshold GARCH Model

Abstract: This paper studies the impact of inflation on inflation uncertainty in a modelling framework where both the conditional mean and conditional variance of inflation are regime specific, and the GARCH model for inflation uncertainty is extended by including a lagged inflation term in each regime. Applying this model to the G7 countries with monthly data from 1970 till 2013, it is found that the impact of inflation on inflation uncertainty differs over the regimes in most of the G7 countries. The findings also pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…threshold has more impact on prices than a lower output growth level. Further, similar to the nonlinear Phillips curve literature, recent studies regarding the effect of inflation on inflation uncertainty (see, Evans (1991), Ball (1992), Evans and Wachtel (1993), Kim (1993), Baillie et al (1996), Chen et al (2008) and Chowdhury and Sarkar (2015)) have shown that this link is also nonlinear, indicating that high inflation increases inflation uncertainty more than that in low inflation. Considering the finding of these two nonlinear relationships along with the Taylor (1979) effect, it can be concluded that output growth might have negative effect on its uncertainty during the periods of economic expansion than those of economic recession.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…threshold has more impact on prices than a lower output growth level. Further, similar to the nonlinear Phillips curve literature, recent studies regarding the effect of inflation on inflation uncertainty (see, Evans (1991), Ball (1992), Evans and Wachtel (1993), Kim (1993), Baillie et al (1996), Chen et al (2008) and Chowdhury and Sarkar (2015)) have shown that this link is also nonlinear, indicating that high inflation increases inflation uncertainty more than that in low inflation. Considering the finding of these two nonlinear relationships along with the Taylor (1979) effect, it can be concluded that output growth might have negative effect on its uncertainty during the periods of economic expansion than those of economic recession.…”
Section: Introductionsupporting
confidence: 56%
“…(), Chen et al . () and Chowdhury and Sarkar ()) have shown that this link is also nonlinear, indicating that high inflation increases inflation uncertainty more than that in low inflation. Considering the finding of these two nonlinear relationships along with the Taylor () effect, it can be concluded that output growth might have negative effect on its uncertainty during the periods of economic expansion than those of economic recession.…”
Section: Introductionmentioning
confidence: 96%
“…However, previous empirical evidence shows that there seem to have mixed results for the relationship between inflation and its uncertainty. Earlier studies have concentrated on advanced economies (e.g., Grier and Perry, 1998;Kontonikas, 2004;Fountas and Karanasos, 2007;Caporale andKontonikas, 2009 andChowdhury andSarkar, 2015). Most of these studies give evidence supporting the Friedman-Ball hypothesis while some studies give evidence in favor of the Cukierman and Meltzer hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of regime switching behavior of inflation while dealing with inflation uncertainty was first addressed by Evans (), and later by Evans and Wachtel (), Bhar and Hamori (), Chen et al . (), Chang and He (), Chang (), and Chowdhury and Sarkar (). Their overall conclusion is that proper attention needs to be paid to the consequences of regime switches; otherwise, the models would seriously underestimate both the degree of uncertainty of inflation and its impact.…”
Section: Introductionmentioning
confidence: 99%